Microstructural characterization and electrochemical properties of Nd0.5Sr0.5Co0.5Mn0.5O3-δ as a novel cathode for SOFCs - Jie Song; Xiufang Zhu; Yuanzhi Song; Pusu Zhao; Fengxia Zhu; Xiaoyan Liu; Xiaojun Sun; Jiming Xu (Materials Research Express, 2020)
The microstructure and electrochemical properties of a novel cathode Nd _0.5 Sr _0.5 Co _0.5 Mn _0.5 O _3- _δ were discussed in the paper. After calcination at 1000 °C, a perfect single crystal was obtained. Some diffraction streaks along [200] and [112] patterns in HR-TEM appeared for the ordering of oxygen vacancies, or as the overlap of B-site cations (Co ^2+ /Co ^3+ and Mn ^2+ /Mn ^3+ ) with stacking fault-derived scattering of ordering. Area-specific resistance (ASR) was 0.023 Ω · cm ^2 when Nd _0.5 Sr _0.5 Co _0.5 Mn _0.5 O _3- _δ was deposited on the electrolyte as the electrode at 700 °C in air. The maximum power density and the maximum OCV were 592.80 mW·cm ^−2 at 650 °C and 0.89 V at 550 °C for a single cell, respectively. Hence, the material Nd _0.5 Sr _0.5 Co _0.5 Mn _0.5 O _3- _δ could be considered as an air-electrode in Intermediate-temperature solid oxide fuel cells (IT-SOFC).